Suppressor of yeast mitochondrial ochre mutations that maps in or near the 15S ribosomal RNA gene of mtDNA. - Fox, T D (1982)
A polypeptide chain-terminating mutation in the yeast mitochondrial oxi 1 gene has been shown to be an ochre (TAA) mutation by DNA sequence analysis. Mitochondrially inherited revertants of this mutation include two types: In the first, the ochre codon has been changed to a sense codon by further mutation in the oxi 1 gene while, in the second, the ochre codon is still present, indicating the occurrence of an extrageneic ochre suppressor mutation. This mitochondrial ochre suppressor, termed MSU1, has been "cloned" in rho- strains of yeast and tested against other oxi 1 mutations. Several additional mutations are also suppressible, and those examined so far are also ochre mutations. MSU1 does not suppress known frameshift or missense mutations at oxi 1. Isoelectric focusing of the gene product (cytochrome oxidase subunit II) from a suppressed-mutant strain indicates that suppression does not involve insertion of charged amino acids. Physical mapping of the mtDNA retained in the MSU1-carrying rho- clones localizes the suppressor mutation to the gene coding the 15S rRNA or a site not more than 300 base pairs from it. No known tRNA genes occur this close to the 15S rRNA gene, and mtDNA from a suppressor-carrying rho- does not hybridize detectably to mitochondrial tRNAs. These results suggest that MSU1 may be an alteration in the 15S rRNA.